Large-scale production of non-conventional edible plants for biodiverse school meals - Ranieri, Guilherme Reis; Madeira, Nuno Rodrigo; Slater, Betzabeth; de Toledo Marchesi, Mariana; Delgado de Oliveira, Maria Angela; Badue, Ana Flávia Borges; Mauad, Thais (Frontiers in Nutrition, 2024)
Introduction School feeding programs are important for ensuring food security and promoting child health and development, particularly in low-income countries. In view of this importance, it is possible to increase the quality of these meals by diversifying the vegetables offered and incorporating underutilized plants to improve dietary diversity and nutritional quality into school meals. Methods This study was carried out using the action research methodology following the implementation and development of the “Inova na Horta” project in the city of Jundiaí, São Paulo, Brazil. The project was based on the existing and functioning physical and organizational structure of a municipal organic farm. Vegetables were selected from among 210 non-conventional species and varieties, which were further selected for continuous production based on 8 nutritional, culinary and cultivation criteria. Results Thirty-four vegetables were selected for continuous cultivation and provisions to the school kitchens. Nine tons of vegetables were produced and provided to 90 municipal schools from 2020–2023. Leafy vegetables accounted for most the production, with a total weight of 6441 kg corresponding to 71.6% of the total harvest. Kitchen teams were trained throughout the project duration. Discussion The feasibility of the production and culinary use of 34 biodiverse, nutrient-rich and underutilized food vegetables for school meals was demonstrated. The selected vegetables are nutrient-rich and contain higher amounts of minerals and proteins than the control vegetables (conventional vegetables), thus complementing several nutrients in school meals. This methodology can be replicated by municipalities of various sizes as a public policy of food and nutritional security associated with the valorization of local biodiversity.